2015
DOI: 10.1136/annrheumdis-2015-eular.3129
|View full text |Cite
|
Sign up to set email alerts
|

SAT0371 Characterization of a SjÖgren's Syndrome-Associated Long Non-Coding RNA at 2P25.1

Abstract: BackgroundSjögren's syndrome (SS) is a common autoimmune disorder characterized by immune-mediated exocrine gland destruction and systemic inflammation contributing to clinical heterogeneity. The complex regulatory mechanisms governing these responses are poorly understood. We previously performed an RNA-sequencing (RNA-seq) study and identified >2,600 differentially expressed (DE) transcripts associated with SS.ObjectivesThis study sought to validate, replicate, and functionally characterize one upregulated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Although some studies have been accomplished in the understanding of miRNA in SS [34,37–39] , the role of long non-coding RNAs (lncRNAs) remained uncharacterized. Ice et al found significant upregulation of the 2p25.1 lncRNA in SS patients ( P = 3.69 × 10 −5 ) compared to healthy controls [40] . Furthermore, this transcript was found highly expressed in CD4 + and CD8 + T cells, and NK cells [40] .…”
Section: Exploring Genomic Biomarkers For Pssmentioning
confidence: 96%
See 1 more Smart Citation
“…Although some studies have been accomplished in the understanding of miRNA in SS [34,37–39] , the role of long non-coding RNAs (lncRNAs) remained uncharacterized. Ice et al found significant upregulation of the 2p25.1 lncRNA in SS patients ( P = 3.69 × 10 −5 ) compared to healthy controls [40] . Furthermore, this transcript was found highly expressed in CD4 + and CD8 + T cells, and NK cells [40] .…”
Section: Exploring Genomic Biomarkers For Pssmentioning
confidence: 96%
“…Ice et al found significant upregulation of the 2p25.1 lncRNA in SS patients ( P = 3.69 × 10 −5 ) compared to healthy controls [40] . Furthermore, this transcript was found highly expressed in CD4 + and CD8 + T cells, and NK cells [40] .…”
Section: Exploring Genomic Biomarkers For Pssmentioning
confidence: 96%